Self-Efficacy and Compliance Fluid Intake Restriction as a Determinant of The Interdialytic Weight Gain (IDWG) Level - Wayunah Wayunah (Universitas Padjadjaran, 2022)
Higher interdialytic Weight Gain (IDWG) is commonly experienced by patients with chronic kidney disease (CKD). Increased IDWG can cause various complications that result in risk of death. CKD patients who had undergoing hemodialysis in the Public Regional Hospital of Indramayu would have different weight gain, but it is not known what factors affect the increase in IDWG. The purpose of this study was to determine the factors that were significantly related to the IDWG level in CKD patients in the Public Regional Hospital of Indramayu. This research design is descriptive-analytic. The number of samples was 86 respondents who were selected by consecutive sampling technique. Data collection tools are questionnaires and the data analysis technique is the Pearson chi-square test. From the result from 86 respondents, it is known that 44 (51.2%) respondents experienced an increase in IDWG level at the mild category (<4%). It is known that the factor influencing to level of IDWG are self-efficacy (p-value = 0.000; 95% CI) and fluid intake compliance (p-value = 0.042; 95% CI). Meanwhile, age, sex, education level, family support, and duration of hemodialysis are not influencing the IDWG level (p-value > 0,05; 95% CI). Self-efficacy and fluid intake compliance are the most significant factor on the IDWG level in CKD patients who had hemodialization. Patients with high self-efficacy can reduce the IDWG level accompanied by compliance with fluid restriction. Recommendation for hemodialysis nurses needs to increase the patient’s self-efficacy in limiting fluid so that can be controlled at the IDWG level.